Effect of School Culture and Non-Physical Work Environment on Teacher Performance Through Motivation: Study at SD An Namiroh Pekanbaru - Junaidi, Junaidi (Proceeding Economy of Asia International Conference, 2026)
Introduction/Main Objectives: This study examines how school culture and the non-physical work environment influence teacher performance, with motivation serving as an intervening variable. The objective is to understand the mechanism through which these organizational factors shape teacher outcomes. Background Problems: The study addresses the question of how school culture, non-physical work environment, and motivation contribute to variations in teacher performance. Research Methods: A quantitative approach was employed involving 49 teachers from SD An Namiroh 3 Pekanbaru. Path analysis using SmartPLS was conducted to evaluate the relationships among variables, supported by tests of significance and model explanatory power. Findings/Results: The results show that school culture significantly affects motivation (t = 2.397; p = 0.017), as does the non-physical work environment (t = 2.109; p = 0.035). School culture does not directly influence performance (t = 1.852; p > 0.05), while the non-physical work environment demonstrates the strongest direct effect (t = 5.605; p < 0.001). Motivation does not directly impact performance but mediates the effect of the non-physical work environment. The model explains 72.3% of the variance in performance (R² = 0.723). Conclusion: The study concludes that strengthening the non-physical work environment and enhancing motivation are critical for improving teacher performance.